(3GdCaYGds - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s ((3ESeGYjd Hf eMeO GdMfGWi s)
(3ChdgG (B:s
(3jHOC HcJGH GdCaYGd ef GdSGde (B: (3HaJM GdYjf ef GdeGVi hVegG ef GdeSJbHd HGH aYd , Hbhdg (B: (3KbH GdTF HGdeKbH hKbHJ GdfGQ JhbOJ KbhHkG s
(3BNQgG (B:s
(3jfJgi HHGH GdJaYdd ef GdeVGYa Hbhdg (B: (3hJdgdg GdSQGH Ci WY hfggJg aJfgfg Ci caaJg aca hGddg CYde HGdUhGH Je cJGH GdeVGYa s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B52s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs